Needs Analysis for Designing Dynamic Game-Based Learning Media on Motion and Force in Junior High School Science - Zarror, Afif Fauzan; Sumaryati, Sri; Sukmawati, Fatma (Universitas Veteran Bangun Nusantara, 2025)
Understanding Motion and Force remains challenging for junior high school students, particularly due to the abstract and multi-representational nature of the concepts. This study aimed to systematically identify learning difficulties, learner characteristics, media usage patterns, and digital habits through the Define stage of the 4-D development model as the foundation for designing game-based learning media. A mixed-methods needs analysis was conducted using classroom observations, a teacher interview, and a questionnaire administered to 93 seventh-grade students. Triangulated findings reveal persistent conceptual difficulties, especially in interpreting motion graphs, distinguishing types of motion, and understanding Newton’s Second Law. Classroom instruction was dominated by teacher-centered practices and static media, which constrained visualization and increased cognitive load. Despite frequent daily smartphone use, students had limited exposure to digital or interactive tools. Nevertheless, 98.9% expressed strong interest in educational games, indicating high readiness for game-based learning environments. The synthesis of front-end, learner, and task analyses highlights critical representational needs, including dynamic visualizations, interactive manipulation of variables, scaffolded conceptual tasks, real-time feedback, and mobile-friendly accessibility. These results provide explicit design specifications that will guide the next stage of media development, ensuring that the resulting game-based learning tool aligns with students’ cognitive, pedagogical, and technological needs.